Efficiency of cryoperenosis depending on various factors - N V Protopopova; E B Druzhinina; U V Mylnikova; N A Boldonova; J A Dvoryanov; K V Krylova; A V Labygina; I I Kovalenko (IP Berlin A.V., 2018)
Materials and methods. The article presents an assessment of the influence of factors on the effectiveness of cryoprenoses. Scientists conducted a retrospective analysis of 149 cryogenic transfer on the basis of the department of Auxiliary reproductive technologies of the Irkutsk Regional Perinatal Center for 2017. Patients signed voluntary consent to participate, the patients were divided into 4 groups, depending on the duration of storage of embryos: group 1 - 57 people, with a shelf life of 1-3 months, group 2 - 29 people, storage period 4-6 months, group 3 - 25 people, the shelf life is 7-11 months, group 4 - 38 people, the shelf life is 12 months or more. The average age of women is 30.69±2.9 years. Selection criteria for research: tubal factor of infertility, frozen embryos. Results. The analysis of cryopreference showed that the age of patients, the quality of transferred devitrified embryos and the duration of storage of cryopreserved embryos have a more important influence.